Assessment of regional right ventricular systolic function in patients with obstructive sleep apnea syndrome using velocity vector imaging. Issue 37 (September 2016) - Li, Junfang; Wang, Zhibing; Li, Yong; Meng, Yuanyuan; Li, Rong; Wang, Wugang; Fu, Xiuxiu
Abstract : Abstract: Obstructive sleep apnea syndrome (OSAS) is the most common type of sleep disorder which is associated with a series of cardiovascular disorders, including right ventricular (RV) dysfunction. However, it is difficult to assess the RV function systematically using a conventional echocardiography because RV has a complex geometrical shape. A case-control study was performed to assess the regional right ventricular potential dysfunction in patients with OSAS using velocity vector imaging (VVI) from March 2014 to October 2015. Sixty-nine patients with OSAS were divided into 3 groups: mild, moderate, and severe according to the apnea–hypopnea index (AHI). A total of 31 cases of healthy subjects were enrolled as the control group. Digital images of apex 4-chamber views were acquired to measure the peak systolic velocity (V), strain (ST), and strain rate (STR) of right ventricular free wall (RVFW) basal, middle, and apical segments using VVI. The peak systolic velocity of RVFW basal segments in the mild OSAS group increased ( t = 2.22, P = 0.049) and gradually reduced in the moderate and severe groups compared with the controls. The values of systolic ST and STR of apical segments decreased in the mild OSAS group compared with the normal control group ( t = 3.30, P = 0.02; t = 3.75, P = 0.01, respectively), and decreased furthermore in the moderate and severe OSAS groups. The change in the right ventricular regional systolic function starts before the development of heart dysfunction and pulmonary hypertension. At the early stage of OSAS, the deformation decreases in the RVFW apical segment, and the peak systolic velocities increase in the RVFW basal segment. The VVI is a sensitive method which is expected to be a worthy technique for early clinical therapy in patients with OSAS.